LEGOSC: Mindstorms NXT robotics programming for artists - Cardoso, Jorge C. S. (2008)
Robotics is an interesting but difficult area for digital artists who generally don’t have much academic background on electronics or computer programming. Digital art students normally use high-level application to program their visual and sonorous installations. This paper presents LegOSC - a tool that allows the control of the Mindstorms NXT robots from any application that uses the Open Sound Control protocol which is implemented by most of those high-level applications. This allows artists to create works which incorporate robotic parts using the familiar programming environment